SIFAT FISIK BATANG DAN CABANG KAYU MAKADAMIA - Andi Detti Yunianti (PERENNIAL, 2006)
Since there have been a big difference between wood production and industrial need, wood diversification plays an important role in handling wood deficiencies. Wood raw material diversification could developed and increased throughout the use of whole parts of the tree including branch. The current study was aimed at understanding stem and branch physical properties (basic density, air-dry specific gravity, air-dry moisture content and shrinkage) of macadamia wood as quality indicators for efficient utilization in the future. For the purpose of the study, parts of stem and branch of the tree were taken from a macadamia tree. Test specimens of stem were cut 50 cm from the ground while that of branch were selected from the largest diameter at 10 cm distance from the main stem of the tree. All samples were tested for their physical properties according to ISO standards, 1975. Results showed that the basic density, air dry specific gravity and longitudinal shrinkage of the branchwood of macadamia were higher than those of the stem. The air-dry moisture content, radial and tangential shrinkage were low on the branchwood. Keywords : Wood Physical Properties, Branchwood , Macadamia Wood